Safety, Tolerability, and Pharmacokinetics of SC1011 (Sufenidone), a Novel Antifibrotic Small Molecule, in Phase 1 Studies in Healthy Subjects - Liu, Yun; Chen, Xiaoning; Tang, Huimin; Jiang, Fan; Tang, Yaqin; Zhu, Huijuan; Du, Yanping; Qian, Hongjie; Liu, Shuyun; Sun, Xiaoshu; Zan, Bin; Zeng, Yuexia; et al. (Clinical and translational science, 2025)
ABSTRACT SC1011 (sufenidone) is a novel pyridone derivative with therapeutic potential for idiopathic pulmonary fibrosis (IPF). Two Phase 1 studies evaluated the safety and pharmacokinetics of single (SAD) and multiple ascending doses (MAD) of SC1011 immediate‐release (IR) and modified‐release (MR) oral formulations in healthy adult subjects. In Phase 1a, subjects were randomized to receive oral SC1011 IR or placebo in SAD (50 mg‐300 mg) or MAD (100 mg and 200 mg) twice daily for 7 days. The Phase 1b study consisted of three treatment groups that received 100, 150, or 200 mg SC1011 MR twice daily for 7 days. SC1011 IR was absorbed rapidly (mean time to maximum concentration, Tmax ≤ 1 h) and eliminated rapidly (mean terminal half‐life, t1/2: 1.23–2.64 h) following 50–300 mg single‐dose administrations. Reduced maximum plasma concentration (Cmax), delayed Tmax, and comparable total exposure were observed with the MR formulation compared with the IR formulation. Both formulations demonstrated dose‐proportional pharmacokinetics at the applied dose ranges, and no obvious accumulation of systemic exposure was observed upon repeated administration. All treatment‐emergent adverse events (TEAEs) with both formulations were mild or moderate in severity, and gastrointestinal reactions were the most frequently reported TEAEs. The tolerability of SC1011 was markedly improved with the MR formulation. Exposure–adverse event (AE) analysis with the most frequent AEs identified Cmax rather than total exposure as a good predictor of AEs. Compared to the IR formulation, SC1011 MR demonstrated improved exposure and tolerability, supporting its further development in patients with IPF.